Optimization of in vitro regeneration protocol of tomato cv. MT1 for genetic transformation - Ahmed, Shiuli; Wan Azizan, Wan Aina Sakeenah; Akhond, Md. Abdullah Yousuf; Juraimi, Abdul Shukor; Ismail, Siti Izera; Ahmed, Razu; Md Hatta, Muhammad Asyraf (Multidisciplinary Digital Publishing Institute, 2023)
The tomato (Solanum lycopersicum L.) is a major crop of global economic significance. The characterization of genes associated with agriculturally important traits is often performed using genetic transformation. To achieve an efficient transformation protocol, three components are required, namely, a regenerable target tissue, a DNA delivery method, and a robust transformant selection system. The present study was conducted to optimize the in vitro regeneration protocol for the tomato cv. MT1. The regeneration capacity of hypocotyl and cotyledon explants was evaluated using a total of 20 concentration combinations of two plant growth regulators (PGRs) added into the basal MSB5 medium, namely, 6-benzylaminopurine (BAP) (0, 1, 2, 3, and 4 mg/L) and indole-3-acetic acid (IAA) (0, 0.05, 0.1, and 0.5 mg/L). The optimal PGRs combinations for the cotyledons and hypocotyls were MSB5 supplemented with 2 mg/L BAP and 0.5 mg/L IAA and MSB5 supplemented with 2 mg/L BAP and 0.1 mg/L IAA, respectively. To determine the minimum inhibitory concentration (MIC) of kanamycin, eight different concentrations (0, 50, 75, 100, 125, 150, 175, and 200 mg/L) were added to the MSB5 supplemented with 2 mg/L BAP and 0.5 mg/L IAA. The MIC for the cotyledons and hypocotyls were determined to be 50 mg/L and 100 mg/L, respectively.